Modeling Term Structures of Defaultable Bonds - Duffie, Darrell; Singleton, Kenneth J. (Review of Financial Studies, 1999)
[This article presents convenient reduced-form models of the valuation of contingent claims subject to default risk, focusing on applications to the term structure of interest rates for corporate or sovereign bonds. Examples include the valuation of a credit-spread option.]